Between Price and Pride: Siri’ as a Culture-driven Factor in Fish Trader Decision-Making - Dahlan, Lukman; Alkam, Rahayu; Ruzika Zaimar, Fina (International Environmental Conferrence on Biosustainability Advancement, 2025)
This study explores the role of Siri’ as a cultural basis for fish traders' pricing decision-making processes. It adopts an ethnomethodological approach to examine everyday reality and how traders produce those realities through their presentations of self and interactions with others in pricing practices. Data were collected through participant observation and in-depth interviews with five key informants. The results of the study identified four practices that manifest Siri’ in the context of fish price decision-making, namely Lempu (honesty), Siamasei(compassion), Sitinaja (fairness), and Reso (effort). From these practices, Bugis fish traders' decision-making is more driven by the culture of Siri’ than by purely economic calculations. Siri’ function as an unwritten, yet effective, practical guideline for everyday economic behavior. This condition challenges the neoclassical assumption that firms tend to maximize profits. Instead, fish traders strive to maintain a balance between dignity, social relations, and business sustainability